Analisis Klasifikasi Massa Batuan dan Potensi Longsor Pada Area Pit Timur Tambang Terbuka PT. Allied Indo Coal Jaya, Kota Sawalunto, Sumatera Barat - Rizki Aldi Saputra; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. Based on observations made on the slopes in the pit area east of the open pit PT. Allied Indo Coal Jaya, found rock slope which has a height of 16 meters, slope angle is 74 and has many weak plane structures that can cause landslides. Therefore it is necessary to analyze the rock mass and the stability of the slope. From the analysis that has been done, the rock mass classification value is 50, with medium quality and safety factor value at saturation condition is 1,117, original condition is 2,779, dry condition is 2,749 and actual condition in field is 1,789. So it can be concluded that the slope condition is stable, except when saturated. Therefore, improvements need to be made in the form of reducing the slope angle to 66º, so that the value of the saturated slope safety factor changes to 1.596.Keywords: Open pit, slope, landslide, rock mass, safety factor